Quality Parameters, Volatile Composition, and Sensory Profiles of Highly Endangered Spanish Citrus Fruits - Marina Cano-Lamadrid; Leontina Lipan; Francisca Hernández; Juan José Martínez; Pilar Legua; Ángel A. Carbonell-Barrachina; Pablo Melgarejo (Journal of Food Quality)
There is very little information available on the chemical composition and the quality attributes of the citrus species studied which are truly endangered in Spain. None of the fruits studied is available for commercial purposes, which is the main interest and novelty of this study. The aim of this work was to fully describe the morphology, volatile composition, and sensory profile of traditional citrus fruits: sour lime (SoLi), sweet lime (SwLi), and sweet lemon (SwLe), to have the information to convince farmers and growers to cultivate these fruits again. The predominant sugar was fructose while citric acid prevails in SoLi and SwLe. Regarding volatiles compounds, monoterpenes, monoterpenoids, and esters predominated in the juices, and these three families plus sesquiterpenes in the peels. The juice of SoLi presented the highest content of esters (14.8%), SwLi juice presented similar values of both monoterpenes and monoterpenoids (46.1 and 46.0%, resp.), and SwLe juice had the highest content of monoterpenes (72.2%). The results demonstrated the high potential of these citrus materials for the agrofood industry. Therefore, it will be possible to recover these vegetal materials at risk of disappearing for potential uses by the food industry and simultaneously help maintaining the biodiversity.